2013
DOI: 10.1016/j.chiabu.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of depressed mothers in home visiting: Impact on psychological distress and social functioning

Abstract: Objectives Depression is prevalent in mothers receiving home visiting. Little is known about the impact of treatment on associated features of maternal depression in this population. The purpose of this study was to examine the impact of a novel, adapted treatment for depressed mothers in home visiting on psychological distress and social functioning. Methods In-Home Cognitive Behavioral Therapy (IH-CBT) was developed to treat depressed mothers in home visiting. A randomized clinical trial design was used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 30 publications
1
48
0
2
Order By: Relevance
“…In addition, they reported increased social support, improved functioning in daily activities, and decreased psychological distress (Ammerman, Putnam, Altaye, Teeters, et al, 2013); these findings were maintained through to the 3-month follow-up (Ammerman et al, 2015). Because IH-CBT and HVP alone did not differ significantly regarding infants’ social and emotional functioning and observed parenting, Ammerman and colleagues (2015) combined data across groups and found that as mothers’ depression improved, there were parallel improvements in their parenting (e.g., more nurturing and stimulating).…”
Section: Interventions To Improve Parenting By Mothers Of Infants Andmentioning
confidence: 95%
“…In addition, they reported increased social support, improved functioning in daily activities, and decreased psychological distress (Ammerman, Putnam, Altaye, Teeters, et al, 2013); these findings were maintained through to the 3-month follow-up (Ammerman et al, 2015). Because IH-CBT and HVP alone did not differ significantly regarding infants’ social and emotional functioning and observed parenting, Ammerman and colleagues (2015) combined data across groups and found that as mothers’ depression improved, there were parallel improvements in their parenting (e.g., more nurturing and stimulating).…”
Section: Interventions To Improve Parenting By Mothers Of Infants Andmentioning
confidence: 95%
“…16,40 Maternal health is improved by more frequent prenatal care, better birth outcomes, and early detection and treatment of depression. 41 Outcome studies have established the effectiveness of home visiting by nurses or community health workers in reducing child maltreatment, 42 improving birth outcomes, 43 and increasing school readiness. 44 A close examination of the evidence of effectiveness published in 2015 by the HomVEE review provides additional insights about the potential benefits and limitations of current models of home visiting.…”
Section: National Evaluation and Evidence Of Effectivenessmentioning
confidence: 99%
“…The most well-researched efforts to date have involved the delivery of cognitive behavioral interventions for depression by trained mental health professionals during home visits (Ammerman et al, 2005) or as an adjunct to home visiting (Tandon, Leis, Mendelson, Perry, & Kemp, 2014). Accumulating results from these initiatives are highly promising, suggesting that enhancing HV with research-supported mental health interventions can be effective in reducing client symptoms of depression (Ammerman et al, 2013; McFarlane, Burrell, Duggan, & Tandon, 2016; Segre, Brock, & O'Hara, 2015; Tandon et al, 2014). However, approaches that integrate psychotherapy into HV require highly trained therapists to provide the intervention, a resource that may be beyond the reach of some state HV systems and local programs.…”
Section: Introductionmentioning
confidence: 99%